Dark-Chocolate-Coated BRS Clara Raisins: Phenolic Composition and Sensory Attributes - Olivati, Carolina [UNESP]; Nishiyama-Hortense, Yara Paula [UNESP]; Soares Janzantti, Natália [UNESP]; da Silva, Roberto [UNESP]; Lago Vanzela, Ellen Silva [UNESP]; Gómez-Alonso, Sergio (MDPI, 2023)
Dark chocolate dragée confectionary was made with BRS Clara raisins pre-treated with extra virgin olive oil (EVOO). The evaluation of the changes in the phenolic composition (flavonols, hydrocinnamic acid derivatives (HCADs), stilbenes and flavan-3-ol monomers, dimers, and proanthocyanidins (PAs)) resulting from the covering process showed that the chocolate coating was responsible for an increase in the concentrations of flavan-3-ols and PAs when compared to just the raisins. For the flavonols and HCADs, a reduction in the total concentration of compounds was observed when comparing the dragées to the raisins. Furthermore, there was a strong influence of chocolate in the qualitative profile with the emergence of new compounds (quercetin-3-pentoside, kampfterol-3-rutinoside, p-coumaric acid, and caffeoyl-aspartate). The combination of these ingredients (raisins and chocolate) resulted in a dark chocolate coated raisin (DC) with good sensory acceptance and a more complex phenolic composition that may positively contribute to its functional quality.
Keywords: Brazilian cultivar; chocolate; dragée; HPLC-DAD-ESI-MS/MS; phenolic composition; raisin